A Model for Predicting Entrepreneurship Intentions based on Social Cognitive Theory and Entrepreneurship Characteristics - Kim-Soon N.; Al-Rawi O.Y.M.; Mostafa S.A.; Ling C.Y.; Al-Dayyeni W.S.; Ali R.R.; Mahmoud M.A.; Al-Rawi B. (Natural Sciences Publishing, 2023)
This research studies whether entrepreneurial characteristics comprising passion, creativity, and self-efficacy are significantly associated with entrepreneurial intentions. Therefore, the final year students from various disciplines from a public university who were potential entrepreneurs and have attended the advance level courses on entrepreneurship were chosen for the data collection. Most of these students have participated in the on-campus business related activities and received some experience through these activities. It was found that there are strong positive correlation between entrepreneurial characteristic factors with entrepreneurial intention. Overall, the R2 of the entrepreneurships characteristics comprising entrepreneurial passion, self-efficacy, and creativity to predict entrepreneurship intention to become an entrepreneur shows very strong explanation power. It implies that this study's proposed model can serve as an assessment tool for selecting students with the higher entrepreneurial intention to engage them in entrepreneurship and activities at the university. 2022, Natural Sciences Publishing. All rights reserved.